A criatividade na pequena empresa: um estudo de caso sobre a percepção dos dirigentes e dos empregados - Piedade Filho, Waldomiro (2006)
The objective of this study is research the creativity in the small family business, what can contribute for the survival of this kind of organization in the nowadays competitive environment. The creativity in companies can have as results the reduction of costs, the development of products and processes, quality improvement and even the creation of new products, among others. In this point of view, the creativity is the generator of innovation, and this process makes an invention rentable for the company. The case study was made in a textile company located in São Paulo and it is part of a traditional sector of the economy. The main objective is to understand how the creativity was experienced and noticed by the high administration and employees. Using semi directed interviews there were an attempt to discover how this small company deals with its employees to encourage the development of creative ideas. The central premise was that the owners of small family business of a traditional sector of the economy, as they centralize the knowledge and power, do not encourage the creativity of their employees, what could be evidenced. Some of the many factors that characterize a favorable environment to the creativity as motivational work in the operational area, autonomy, valuation of the training activity, rewards for creative individuals and, specially, support from the high administration; were not found in the textile company studied. The following study intend to contribute to put the focus on a subject still little explored in the literature researched